Up and running with Autodesk Inventor Simulation 2010 : a step-by-step guide to engineering design solutions - Younis, Wasim (Elsevier ; Butterworth-Heinemann, 2009)
Inventor Simulation is an essential part of the Autodesk Digital Prototyping process. It allows engineers and designers to explore and test components and products virtually, visualizing and simulating real-world performance. Up and Running with Autodesk Inventor Simulation 2010 is dedicated to the requirements of Inventor users who need to quickly learn or refresh their skills, and apply the dynamic simulation, assembly analysis and optimization capabilities of Inventor Simulation 2010. Step-by-step approach gets you up and running fast Discover how to convert CAD models to working digital prototypes, enabling you to enhance designs, reduce over design, failure, and the need to create physical prototypes Extensive real-world design problems explore all the new and key features of the 2010 software, including assembly stress analysis; parametric optimization analysis; creating joints effectively; avoiding redundant joints; unknown force; logic conditions; and more. Tips and guidance you to tackle your own design challenges with confidence Companion site (elsevierdirect.com/companions) provides Simulation datasets for the design problems in the book that enable you to apply, experiment and manipulate solutions, and move on to solving your own design problems. Inventor Simulation is an essential part of the Autodesk Digital Prototyping process. It allows engineers and designers to explore and test components and products virtually, visualizing and simulating real-world performance.